2021
DOI: 10.21475/ajcs.21.15.04.p2789
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the season on establishment of some turf grasses under the climatic conditions in eastern Morocco

Abstract: The turfgrass establishment is an important criterion for the choice of turfgrass species. The faster a lawn is established the more benefits it has to offer for landscapers. The objective of this work is to study the growth speed and development of six species. Four of them are cool-season ones (temperate): Lolium perenne, Festuca arundinacea, Agrostis stolonifera and Poa pratensis while the other two are warm-season ones (tropical): Pennisetum clandestinum and Cynodon dactylon. The species are seeded in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As a rule, warm season turfgrasses perform well in the summer on average, whereas cool-season turfgrasses do well during the coldest months (Richardson et al, 2008;Charif, 2021). Some researchers have observed that warmseason grass species use less water to generate the same dry matter weight due to their distinct physiology, therefore they are more suitable to Mediterranean climates and have greater recovery when compared to cool-season turf species (Croce et al, 2004;Turgeon, 2012;Volterrani and De Bertoldi, 2012;Lulli et al, 2012;Fontanelli et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…As a rule, warm season turfgrasses perform well in the summer on average, whereas cool-season turfgrasses do well during the coldest months (Richardson et al, 2008;Charif, 2021). Some researchers have observed that warmseason grass species use less water to generate the same dry matter weight due to their distinct physiology, therefore they are more suitable to Mediterranean climates and have greater recovery when compared to cool-season turf species (Croce et al, 2004;Turgeon, 2012;Volterrani and De Bertoldi, 2012;Lulli et al, 2012;Fontanelli et al, 2017).…”
Section: Resultsmentioning
confidence: 99%